Immigration and Transnationalism: Rethinking the Role of the State in Latin America. (18th March 2013) - Weeks, Gregory; Weeks, John
Abstract As more Latin American migrants make their way to the United States, the issue of transnationalism has received increased scholarly attention. Transnationalism refers to the delinking of the individual from his or her government and an increase in international ties as a result of the economic globalization that promotes the movement of people, goods, money, and ideas. Prevailing consensus is that the state, particularly in Latin America, is weakened by transnationalism because individuals are freer than ever from state control. This article argues that examining Latin American emigrant policies yields a different conclusion, namely that the state's response to transnational pressures has made governments more active and relevant in certain ways than in the past. Studies of transnationalism must therefore incorporate state strategies for a better understanding of its impact on Latin American governments.